1999
DOI: 10.1046/j.1432-1327.1999.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of cytosolic phospholipase A2 in platelets is mediated by multiple stress‐activated protein kinase pathways

Abstract: Stress-activated protein kinases (SAPKs) are stimulated by cell damaging agents as well as by physiological receptor agonists. In this study we show that human platelets contain the isoforms SAPK2a, SAPK2b, SAPK3 and SAPK4 as determined by immunoblotting with specific antibodies. All four kinases were activated in thrombin-stimulated platelets whereas only SAPK2a and SAPK2b were significantly stimulated by collagen. All four isoforms were able to phosphorylate wild-type human cPLA 2 in vitro, although to diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
53
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 41 publications
6
53
0
Order By: Relevance
“…We have recently reported that cPLA2 is phosphorylated to a similar degree on Ser-505 and Ser-727 in human platelets in response to collagen and thrombin and through a pathway that is partially sensitive to inhibitors of p38-2a/2b (16,19). The inhibition data suggest that the Ser-727 kinase is activated by p38-2a/2b in platelets.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…We have recently reported that cPLA2 is phosphorylated to a similar degree on Ser-505 and Ser-727 in human platelets in response to collagen and thrombin and through a pathway that is partially sensitive to inhibitors of p38-2a/2b (16,19). The inhibition data suggest that the Ser-727 kinase is activated by p38-2a/2b in platelets.…”
Section: Discussionmentioning
confidence: 90%
“…2C, right panel). MNK1 and Related Kinases Phosphorylate cPLA2 on Ser-727 in Vitro-Inhibition of cPLA2 phosphorylation on both Ser-505 and Ser-727 by p38 inhibitors suggests that the Ser-727 kinase may be one of the growing family of protein kinases that are activated by MAPK family members (16,19). cPLA2 in thrombin-and collagen-stimulated platelets is phosphorylated on Ser-505 by one or more p38 isoforms and not by ERK1 or ERK2 P i and then either not stimulated (E) or stimulated (q) with 1 M A23187 for 10 min.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations